Studi Mekanisme Kelongsoran dan Alternatif Penanganan Tanah Lunak Pada Ruas Jalan Tol Indrapura – Kisaran (STA 112+850 – STA 112+900) - Haririi, Adnan; Wahyudi, Herman; Lastiasih, Yudhi (Jurnal Manajemen Teknologi & Teknik Sipil, 2025)
Embankment stability is a critical aspect of transportation infrastructure projects, especially in constructing on soft soil. Soft soil has low bearing capacity, high compressibility and low permeability. These characteristics increase the risk of structural failure, such as landslides and excessive settlement necessitating appropriate reinforcement methods. Beyond safety consedirations, soil strengthening must also factor in cost-effectiveness and construction time  to ensure an efficient and economical approach. This study aims to evaluate the effectiveness of Prefabricated Vertical Drain (PVD), geotextile, spun pile, as well as a combination of PVD and geotextile reinforcement methods. Field investigations and laboratory test provided soil and geometric data. This data is used as input in modeling using a finite element approach with Plaxis 2D software. The analysis results include safety factor (SF) values, ​​which are then calculated for strengthening costs and implementation time. A multi-criteria analysis is employed to determine the most optimal reinforcement method based on SF, cost, and implementation duration. The results indicate that the combination of PVD and geotextile provides the highest value, with a safety factor of 1.73, construction costs of IDR 1.57 billion, and implementation duration of 90 days. This strengthening is able to balance the three aspects considered. The combination of PVD which accelerates consolidation and geotextiles which strengthen the embankment structure has been proven to increase stability without significantly increasing costs. These findings contribute to the optimization of soft soil strengthening strategies in selecting efficient and economical strengthening methods.